THE SHEEP AND GOAT FARMING SECTOR IN ROMANIA – A NEW DEVELOPMENT PERSPECTIVE - Mariana GRODEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the period 2003-2017, Romania became an important export source of live sheep and goats, both for the intra-Community trade and for third countries in particular. From food security perspective, for Romania, sheep and goat meat (accounting for 3.5% of total meat consumption in the year 2016) has a particular importance both for dietary diversification and for the complex contribution to putting into value the country’s agricultural resources, the sheep species having the exceptional capacity to valorize the land from the areas with natural handicaps (80% of these areas are valorized by the ovine species). Although Romania ranks 6th in EU-28 in terms of total sheep and goat herds, it ranks 10th in terms of meat production (in carcass equivalent), yet on the rise compared to the pre-accession period. Considering that self-sufficiency in sheep and goat meat on the EU-28 market is only 88% and demand is increasingly higher on the markets from Asia, South America and Middle East, Romania must capitalize on these opportunities and develop its sheep and goat sector on the long term. The growth of middle-income population from Asia, Latin America and Middle East and the increasing demand of ovine meat implicitly represent an export opportunity that Romania has to valorize, also having in view that Romania, as supplier of live animals, is also appreciated for raising animals under extensive grazing system.